2017
DOI: 10.3390/md15060182
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diseases of Bivalve Mollusks: Infections, Immunology and Antimicrobial Defense

Abstract: A variety of bivalve mollusks (phylum Mollusca, class Bivalvia) constitute a prominent commodity in fisheries and aquacultures, but are also crucial in order to preserve our ecosystem’s complexity and function. Bivalve mollusks, such as clams, mussels, oysters and scallops, are relevant bred species, and their global farming maintains a high incremental annual growth rate, representing a considerable proportion of the overall fishery activities. Bivalve mollusks are filter feeders; therefore by filtering a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(102 citation statements)
references
References 271 publications
(287 reference statements)
1
99
0
2
Order By: Relevance
“…Here, we observed that exposure to either source of copper followed by a 24 h exposure to the pathogenic bacteria Vibrio tubiashii caused a slight, but not significant increase in bacteria proliferation indicating that copper exposure negatively impacts the immune system health preventing bivalve species from effectively fighting off infection. Some pathogens found in bivalves can cause illness in humans as well . If concentrations of nanoparticle pollution increase in the environment, there could be a greater risk to humans who consume shellfish products, since pathogenic bacteria are part of the natural environment and weakened mussels would not be able to prevent their accumulation in the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we observed that exposure to either source of copper followed by a 24 h exposure to the pathogenic bacteria Vibrio tubiashii caused a slight, but not significant increase in bacteria proliferation indicating that copper exposure negatively impacts the immune system health preventing bivalve species from effectively fighting off infection. Some pathogens found in bivalves can cause illness in humans as well . If concentrations of nanoparticle pollution increase in the environment, there could be a greater risk to humans who consume shellfish products, since pathogenic bacteria are part of the natural environment and weakened mussels would not be able to prevent their accumulation in the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…No treatment, sterilization and filtration of inflow water (Zannella et al, 2017) antimicrobials have played a crucial role in prevention, treatment, and control of animal diseases caused by microorganisms. Due to certain advantages, such as exact targeting of pathogens, wellknown mechanisms of activity and desired stability, antimicrobials have justified their usage in food animals and aquaculture, thus playing a main part in the prevention and treatment of bacterial and parasitic diseases.…”
Section: Nocardiacrass Ostreaementioning
confidence: 99%
“…The effectiveness of implemented FSMSs to eliminate V. parahaemolyticus or reduce its concentration in oysters remains a challenge because of increasingly complex interactions among foodborne pathogens, food, vehicles, and environmental conditions (Froelich & Noble, 2016; Zannella et al., 2017). Challenges in the food safety management of oysters are also complicated by the dynamic operating environment as well as the increasing and changing consumer demands and expectations (Froelich & Noble, 2016).…”
Section: Factors Affecting the Accumulation Of V Parahaemolyticus Inmentioning
confidence: 99%